Reaching for the SDGs : The Untapped Potential of Tanzania’s Water Supply, Sanitation, and Hygiene Sector - World Bank (Washington, DC, 2017)
The purpose of the document is to lay out the findings from this diagnostic exercise. Its key messages include stressing the need to reach higher to achieve the Sustainable Development Goal (SDG) targets for water and sanitation in the light of little improvement in the Millennium Development Goal (MDG) era; the lack of access to improved water for rural dwellers and the issues with quality, affordability and reliability of water services for urban dwellers, and how this is linked with the overreliance on an informal service provider market; the lack of improved sanitation in the population with 80% still reliant on rudimentary and unsafe facilities; the identification of rurality and poverty as the primary drivers of low WASH coverage with an in-depth data-based and political economy analysis on why water point failure in rural Tanzania is so high (20% of all water points fail in the very first year of operation); improved WASH can lead to broad knock-on effects on productivity and human development in Tanzania, in particular for reducing chronic malnutrition in children under five; identifies the importance of emphasizing improved WASH in public spaces also such as in schools and health centers; identifies how shortcomings in the decentralization process for Tanzania’s WASH sector have impacted its capacity to deliver services, and how these bottlenecks may be unblocked. It then makes a series of recommendations in order to deliver a better service.